2003
DOI: 10.1046/j.1537-2995.2003.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of RBCs and FFP with whole blood during liver transplant surgery

Abstract: Whole blood, when compared with component therapy, is associated with fewer donor exposures yet provided equally effective replacement therapy for blood loss in liver transplantation patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 9 publications
0
26
0
1
Order By: Relevance
“…A total of 19 comparator studies reported 22 outcomes of the effect of FFP on allogeneic transfusion requirements [22,23,30,35-37,39,41,43,44,47,49,50,64-69]. These requirements were reported as intraoperative, postoperative or total (studies in which the requirements were reported for the whole perioperative period).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 19 comparator studies reported 22 outcomes of the effect of FFP on allogeneic transfusion requirements [22,23,30,35-37,39,41,43,44,47,49,50,64-69]. These requirements were reported as intraoperative, postoperative or total (studies in which the requirements were reported for the whole perioperative period).…”
Section: Resultsmentioning
confidence: 99%
“…However, the results of this study are still valuable for autologous transfusion and the many clinical settings, particularly in developing countries [35] where allogeneic whole blood is still mainly employed. Furthermore, the use of whole blood is gaining renewed interest in developed countries [36][37][38] because it has been shown that leukocyte depletion results in a considerably improved plasma quality in whole blood [39]. cells lose their deformability during storage has been consistently shown by indirect methods using filtration techniques [20] or the LORCA system [21].…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of blood components used is also variable, and some authors have recently suggested that the use of whole blood would actually be more appropriate than RBC and fresh-frozen plasma (FFP) units for liver transplantation [27]. The variability can be partly attributed to a specific patient population or surgical techniques [11 ,21,24].…”
Section: Variability In Transfusion Practicesmentioning
confidence: 99%